Pendidikan dan Pengembangan Potensi Anak Usia Dini - Atabik, Ahmad (THUFULA, 2014)
Developing talents and interests of children aims to make childrenlearn in the field of interest and in accordance with the abilities, talents andinterests they have. In educating children into reliable individuals, parentshave a formidable task and play a decisive role. Parents are required tounderstand the character of the child in the future, recognizing their rights andthen seek the creation of an educational environment that nurtures all aspectsof development that includes the mental, interests, creativity and optimallybalanced manner. In addition to the child’s physical development, cognitionand psychomotor, parents also need to pay attention to affective and spiritualaspects that must still taught by his/her parents to let him/her become resilientindividuals in the world affairs and religion. This article, in addition, providesan overview of ways to develop children, interests, talents and creativity alsosee how the Qur’an gives spiritual guidance to children since childhood, asillustrated by Luqman education to his son.